Analisis Keunggulan Produk Pegadaian Dalam Persaingan UPC Dengan Menggunakan Teknik Competitive Profile Matrix (CPM) Di UPC Karang Lewas dan UPC Alun-Alun Purwokerto - Saputri, Andina Velisha; Khasanah, Anisa Cahyawiru; Raihan, Ziddan Ni’am; Shafrani, Yoiz Shofwa (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the superiority of Pegadaian products in competition between Branch Service Units (UPC) using the Competitive Profile Matrix (CPM) technique at UPC Karanglewas and UPC Alun-Alun Purwokerto. The approach used is descriptive qualitative through case studies, with data collection through in-depth interviews, observation, and documentation. CPM analysis is carried out by identifying key success factors such as service quality, product variety, price, promotion, ease of access, company reputation, and digital product innovation. The results of the study show that UPC Karanglewas has a stronger competitive position with a CPM score of 3.65 compared to UPC Alun-Alun Purwokerto which obtained a score of 3.25. The main advantages of UPC Karanglewas lie in a more complete product variety, ease of access, and digital innovation, while UPC Alun-Alun Purwokerto excels in promotion. This study recommends that each UPC strengthen product differentiation, increase digital service innovation, and optimize promotional strategies to strengthen competitiveness in the national pawn.